Multimodal texts with a suggestive orientation in the information space of wartime Ukraine - Snytko , Olena; Pohorilova , Mariia (Current issues of Ukrainian linguistics: theory and practice, 2023)
The article presents an analysis of multimodal texts with a suggestive orientation in the information space of wartime Ukraine. These texts effectively influence society in a positive way and objectify the narratives that are emotionally rich in description. Multimodal patriotic texts are broadcast through classical and new media, as well as social networks, combining differently encoded information (visual, verbal, and musical text). It has been found that the basic and most important means of suggestive influence is the rhythm of the text, which is created by means of different codes. Rhythm permeates all levels of the text and ensures the result of the recipient's psycho-emotional perception of certain suggestively marked meanings. Rhythm as a proportional alternation of certain elements of the text is "comprehended" by the addressee primarily on the emotional level; the rhythmic structure of the text implies "text assembly", which begins with the unification of the relevant content parts and ends with the creation of a new content unit, i.e. the "text concept". It has been proved that multimodal texts based on a complex of suggestive techniques are associated with the so-called "iconic turn" in communication, i.e. focus on various kinds of visual components of the communication process. The interaction of codes creates a unique information product, the semantics of which cannot be conveyed by means of only one of the codes. Multimodal texts with a suggestive orientation have an extremely wide audience; they represent a quick response to certain wartime crises; they use artistic means to outline the prospects for the wartime crisis development; they embody the relevant emotions of a mentally traumatized society; they objectify the content of events in a vivid and imaginative way; they appeal to the cultural roots of the nation and make extensive use of folklore elements; they enhance the psycho-emotional state of the society and provide multiple reproductions, exercising a long-lasting suggestive influence.
Keywords: Multimodal text, crisis communication, suggestive influence, means of suggestion in a multimodal text.